2012
DOI: 10.1590/s0103-84782012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Persistência de agrotóxicos utilizados na cultura do milho ao parasitoide Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae)

Abstract: II Persistência de agrotóxicos utilizados na cultura do milho ao parasitoide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 3 publications
2
6
0
4
Order By: Relevance
“…These authors also classified chlorfenapyr as slightly harmful (class 2). Stefanello Júnior et al (2008a) showed that triflumuron did not affect T. pretiosum parasitism capacity when tested females were exposed to triflumuron-treated host eggs; this was similar to the findings of the present Sterk et al (1999) in which class 1 = harmless, class 2 = slightly harmful, class 3 = moderately harmful, and class 4 = harmful. 3 Figures followed by the same letter, lower case in columns and upper case in rows, show no differences between them according to Scott-Knott test (P > 0.05) (Scott and Knott, 1974); CVmaternal generation (%) = 35.9 and CVF1 generation (%) = 27.2.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These authors also classified chlorfenapyr as slightly harmful (class 2). Stefanello Júnior et al (2008a) showed that triflumuron did not affect T. pretiosum parasitism capacity when tested females were exposed to triflumuron-treated host eggs; this was similar to the findings of the present Sterk et al (1999) in which class 1 = harmless, class 2 = slightly harmful, class 3 = moderately harmful, and class 4 = harmful. 3 Figures followed by the same letter, lower case in columns and upper case in rows, show no differences between them according to Scott-Knott test (P > 0.05) (Scott and Knott, 1974); CVmaternal generation (%) = 35.9 and CVF1 generation (%) = 27.2.…”
Section: Resultssupporting
confidence: 92%
“…When chlorpyrifostreated host eggs were offered to these females 48 h after treatment, a decrease of 96.9% was observed in parasitism capacity and the compound was considered moderately harmful (class 3) (Table 1). Moura et al (2006) andStefanello Júnior et al (2008a;2008b) also observed that chlorpyrifos drastically reduced T. pretiosum parasitism capacity and classified the pesticide as harmful (class 4).…”
Section: Resultsmentioning
confidence: 96%
“…This is highly relevant, given that weeds are the main limiting factor for rice yield, and weed control is generally performed using herbicides (Sosbai 2014). Low toxicity to egg parasitoids in different developmental stages was also reported for herbicides registered for soybean (Carmo et al 2009, Magano et al 2013) and maize (Stefanello Júnior et al 2008b and.…”
Section: Resultsmentioning
confidence: 58%
“…and Trichogramma spp. (Moura et al 2006, Giolo et al 2007, Stefanello Júnior et al 2008a, Preetha et al 2009, Carmo et al 2010, Koppel et al 2011, Goulart et al 2012, Oliveira et al 2013. As reported by Stefanello Júnior et al (2008a), this toxicity originates from the similarity in the transmission mode of nerve impulses not only between the different orders of insects, but also between the various animal phyla.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation